Risk factors for the Development of multidrug-resistant tuberculosis in Colombia 2008 A 2011 (2016)
Objective Determining the risk factors associated with developing multidrug-resistant tuberculosis in people aged over 18 years affiliated to 3 Colombian health insurance companies between 2008 and 2011. Methods The study involved a matched case-control design (1 case to 4 controls). Patients were identified from 3 health insurance companies’ tuberculosis program database; this gave 45 cases and 180 controls. Demographic, socioeconomic and clinical variables were evaluated. Results The median age for cases was 43 years (39.5 years for controls); males predominated in cases (73.3 %) while women predominated in controls (51.1 %). A statistically significant association was found between multidrug-resistant tuberculosis and being male (4.47 adjusted OR; 1.01-19.75 95 %CI), having subsidized social security cover (57.6 adjusted OR; 4.6-71.28 95 %CI) and having had prior treatment for tuberculosis (56.2 adjusted OR; 10.03-314.79 95 % CI]. Conclusions Prior treatment for tuberculosis and being male were risk factors for developing multidrug resistance. Further studies are needed with the Colombian health system to clarify the findings with respect to being affiliated to a subsidized health system and the development of multidrug resistant tuberculosis. © 2016, Universidad Nacional de Colombia. All rights reserved.